Protective effects of sevoflurane conditioning against myocardial ischemia-reperfusion injury: a review of evidence from animal and clinical studies - Lin, Jiefu; Li, Xia; Yang, Yuhui; Ge, Zhi-dong; Liu, Danyong; Yang, Changming; Zhang, Liangqing; Xia, Zhongyuan; Xia, Zhengyuan (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2025)
Pharmacological interventions with the inhaled anesthetic sevoflurane, widely used in cardiac surgery, have been reported to mimic the cardioprotection produced by ischemic conditioning against myocardial ischemia–reperfusion injury. Beneficial effects of sevoflurane conditioning vary with dose, time window and duration and have been reported in a variety of studies involving both laboratory experiments and clinical trials. However, sevoflurane conditioning effects are impaired or lost in subjects with diabetes in both laboratory and clinical settings with mechanisms incompletely understood. This article summarizes the major findings investigating sevoflurane-induced myocardial protection. Our aim is to provide a better understanding of the interrelated but poorly described sevoflurane conditioning signaling pathways. Moreover, this may facilitate the development of more effective therapeutic or preventive strategies for myocardial ischemia-reperfusion injury.